(3JaSjQ ShQI GdaGJMIs
(3ChdgG (B:s
(3GdMeO ddg efRd GdcJGH eHjfkG hJHjGfkG hHYO aGdbUO PcQ TF ef JaSjQ GdaGJMI ETGQI hbO LGA CfgG GdSHY GdeKGfi hGdbQBf GdYXje s
(3BNQgG (B:s
(3dCedFf Lgfe ef GdLfI hGdfGS CLeYjf (B" (3hGddg jaYd eG jTGA hjMce eG jQjO gPG eG GfJgi Edjg GdbUO hGdETGQI dHYV eG SfM ai JaSjQ GdaGJMI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HBNQg fbhds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdeLGejYs